Comparison of angle-closure detection between automated gonioscopy and anterior-segment optical coherence tomography - Yuki Takagi; Ryo Asano; Yui Morioka; Yukihiro Sakai; Sho Yokoyama; Kei Ichikawa; Kazuo Ichikawa (PLoS ONE, 2025)
Purpose To investigate the concordance between angle-closure assessments based on GS-1 gonioscope images and those obtained with anterior-segment optical coherence tomography. Study design Retrospective clinical study. Methods We included 33 patients (53 eyes) who visited Chukyo Eye Clinic during 2020–2024, were suspected of having angle closure, and underwent anterior-segment optical coherence tomography (CASIA2 Advance STAR Analyzer) and GS-1 examinations. The 16-directional images captured with the GS-1 were divided into two halves, creating 32 directions, which were rearranged to correspond with those obtained via anterior-segment optical coherence tomography. Agreement between evaluations was analyzed using Cohen’s κ, and the area under the receiver operating characteristic curve was evaluated. Anterior-segment optical coherence tomography images were manually corrected, and eyes with areas classified as “narrow” or “closed” were categorized as angle closure. With the GS-1, two glaucoma specialists independently reviewed the images. Areas in which the posterior trabecular meshwork was obscured in more than half of the image (Scheie classification grades III–IV) were judged indicative of angle closure. Results We included 1,660 directions from 53 eyes in the agreement analysis. The proportion of directions judged as angle closure was 57.0% with anterior-segment optical coherence tomography and 46.1% with the GS-1. Cohen’s κ for inter-test agreement was 0.173 (95% confidence interval: 0.128–0.218), and the area under the receiver operating characteristic curve was 0.588 (95% confidence interval: 0.561–0.615). Conclusion Analyses using anterior-segment optical coherence tomography yielded more frequent classifications of angle closure than evaluations based on GS-1 gonioscopic images.